Metal Oxysulfides: From Bulk Compounds to Nanomaterials - Larquet, Clément; Carenco, Sophie (Frontiers in Chemistry, 2020)
This review summarizes the syntheses and applications of metal oxysulfides. Bulk compounds of rare earth and transition metals are discussed in the first section. After a presentation of their main properties and applications, their structures are presented and their syntheses are discussed. The second section is dedicated to the growing field of nanoscaled metal oxysulfides. Synthesis and applications of lanthanide-based nanoparticles are more mature and are discussed first. Then, works on transition-metal based nanoparticles are presented and discussed. Altogether, this review highlights the opportunities offered by metal oxysulfides for application in a range of technological fields, in relation with the most advanced synthetic routes and characterization techniques.